A multicenter study of malignant oral and maxillofacial lesions in children and adolescents. (December 2017) - de Arruda, José Alcides Almeida; Silva, Leni Verônica de Oliveira; Kato, Camila de Nazaré Alves de Oliveira; Schuch, Lauren Frenzel; Batista, Aline Carvalho; Costa, Nádia Lago; Tarquinio, Sandra Beatriz Chaves; Rivero, Elena Riet Correa; Carrard, Vinícius Coelho; Martins, Manoela Domingues; Sobral, Ana Paula Veras; Mesquita, Ricardo Alves
Highlights: The study reports epidemiological multicenter data for the Brazilian population. It assists pediatric oncologists by providing diagnostic tendencies. Mucoepidermoid carcinoma was the most common malignant oral lesion. Abstract: Objectives: To investigate the frequency of malignant oral and maxillofacial lesions among children and adolescents from representative geographic regions of Brazil. Materials and Methods: A retrospective study was conducted on biopsies obtained from 1990 to 2016 at six Brazilian oral and maxillofacial pathology referral centers. A total of 85, 105 biopsy specimens from children and adolescents were analyzed. Gender, age, anatomical location, symptomatology and histopathological diagnosis were evaluated. Data were analyzed using descriptive statistical methods. Results: Fifty-eight (0.06%) malignant oral and maxillofacial lesions were diagnosed in children (19%) and adolescents (81%). The lesions were more frequent among females (60.3%) and adolescents. The most prevalent lesions were mucoepidermoid carcinomas (22.4%), osteosarcomas (13.8%), squamous cell carcinomas (12.1%), and Burkitt's lymphomas (12.1%). The most commonly affected sites were the palate (19%), mandible (13.8%), and maxilla (13.8%). Almost half the patients were asymptomatic. Conclusion: Pediatric oral and maxillofacial malignant lesions were infrequent and showed wide diversity, with a prevalence of mucoepidermoid carcinomas. Analysis of malignant lesions in children and adolescents helps pediatric dentists and oncologists to obtain a better understanding of such lesions and to reduce the time for diagnosis, with a consequent improvement of prognosis.